TOURISTS’ SHOPPING IN THAILAND: A STUDY TO INVESTIGATE JAPANESE TOURISTS’ EXPECTATION AND PERCEPTION ON PRICE AND PROMOTION ELEMENTS OF THAI PRODUCTS - Pakin Witchayakawin (Universitas Gunadarma, 2011)
This research aims to identify the relationship between the prices of Thai merchandise and promotion elements, and Japanese tourists’ expectations and perceptions. Japanese tourists were targeted sampling of this research. It focuses on inbound Japanese tourists, in general, to shop in Thailand, specifically in Bangkok. The independent variables of the research are age, gender, career orientation and educational level. The dependent variables include price, elements of promotion, expectation of product and service quality, as well as perception of product and service quality. The survey instrument for this research is only self-administered questionnaires in Japanese language. The questionnaires were distributed by tourist guides during tours, and by researcher of this research at the Grand Palace in Bangkok. The statistical analysis techniques of this research include One-way ANOVA, Independent Sample t-test and Pearson Correlation. This research, by One-way ANOVA, shows that Japanese tourists with different career orientations have different expectations of the elements of promotion and product quality, including different perceptions of service quality. In addition, through the independent sample t-test, it is learned that Japanese tourists of different gender have different expectations and perceptions of the elements of promotion. The relationship between the price of Thai merchandise and Japanese tourists’ expectations and perceptions on beginning their shopping in Thailand is significant. From this research, merchandise and retail organizations should manage and develop products involved with service quality because Japanese tourists have a different view towards product and service quality according to diversity of career orientation. Future researchers should seek more information about tourists’ expectations of tourism activities such as night safari and theme park. Insight into travelers’ needs and their specific expectations and the perceptions of each particular unit of the visitor market should be explored more fully in order to learn marketing strategies to sustain competition amongst rivals.